ASSESSMENT OF MARKETING EFFICIENCY OF SMOKED FISH AMONG ARTISANAL FISHERFOLKS IN OGUN WATERSIDE LOCAL GOVERNMENT AREA OF OGUN STATE, NIGERIA - OLAOYE, O. J; ADELAJA, O. A; ASHAOLU, O. F; IKENWEIWE, N. B; ASHLEY-DEJO, S.S. (Nigerian Journal of Fisheries, 2015)
This study assessed marketing efficiency among artisanal fisher folks in Ogun waterside. Purpose sampling method was used to select fish processors from fishing communities in Ogun waterside. One hundred and twenty eight fish processors were randomly sampled using interview schedules. Data collected were analyzed using descriptive statistics, profitability indices and inferential statistics. The study revealed that the mean age, household size and processing experience of fish processors were 35 ± 0.76, 5 ± 0.12 persons and 16 ± 0.53 years respectively. Hundred percent of the fish processors were female, 84.4% were married, and 67.9% were educated. Profitability indices were: Benefit Cost Ratio 1.73, Rate of Return on Investment 0.73, Net Profit Margin 0.42 and Marketing Efficiency 0.58. Over 60.0% of the processors sold their processed fish directly to wholesalers. Major constraints faced include inadequate finance, lack/high cost of modern processing facilities and high cost of transportation. It was show that there was no significant association between marketing efficiency and marital status (χ2 = 6.543, p > 0.05), educational level (χ2 = 10.994, p > 0.05) and there was a significant association between marketing efficiency and mode of fish processing (χ2 = 47.842, p < 0.05). Significant relationship existed between constraints faced by fish processors and marketing efficiency at p < 0.05. Fish processors should be encouraged to form themselves into viable cooperative societies, and this will enable them enjoy economics of scale, freedom from exploitation by the middlemen.